Les liaisons dangereuses na Tela: ligações 'perigosas' entre cinema e literatura - Bulhões, Marcelo [UNESP] (My University, 2012)
The purpose of this article is to comment on the film adaptation by director Stephen Frears of the 18th-century novel Les liaisons dangereuses (in English, Dangerous Liaisons) by Choderlos de Laclos. It compares the film composition to the basic formal aspects of the novel. If, on one hand, Frears’ 1988 film adaptation breaks away from Laclos’ epistolary novel for being aligned with the standard elements of the classical cinema, on the other, it reveals a surprising affinity to the literary work: the relation with the theatrical language.

Comentar a adaptação cinematográfica de As ligações perigosas, romance do século XVIII, de Choderlos de Laclos, realizada por Stephen Frears, é o propósito deste artigo. Interessa cotejar a composição cinematográfica aos aspectos formais básicos do romance. Se a adaptação deFrears, no filme lançado em 1988, marca um efeito de afastamento do romance epistolar de Laclos por se alinhar ao padrão do cinema clássico, em outro ponto o filme revela uma curiosa ligação com a obra literária: a relação com a linguagem teatral.
Keywords: Audiovisual adaptation; Cinema; Epistolary novel; Adaptação audiovisual; Cinema; Romance epistolar